Enhanced photocatalytic property of hybrid graphitic C3N4 and graphitic ZnO nanocomposite: the effects of interface and doping. (5th April 2018) - Cui, Jie; Liang, Shuhua; Sun, Shaodong; Zheng, Xing; Zhang, Jianmin
Abstract: Using first-principles calculations, we present a potential new way to improve the photocatalytic efficiency of the g-C3 N4 sheet by coupling with the g-ZnO sheet to form heterojunction nanostructure followed by the addition of N atom at an atomic level. The result indicates the g-C3 N4 /g-ZnO heterojunction is a staggered band alignment (type II) structure and a polarized field is generated by the electrons transfer across the interface simultaneously, which facilitate the separation of e − –h + pairs and promote the photocatalytic activity. Furthermore, a great difference in energy levels between redox potentials and band edges of the C3 N4 /g-ZnO nanocomposite ensures that the water splitting/CO2 reduction reaction is energetically favored. In addition, through the incorporation of nitrogen dopant, the g-C3 N4 /N-g-ZnO nanocomposite displays desirable properties. The N-derived doping peak causes a decrease of the band gap width of the g-C3 N4 /g-ZnO nanocomposite, resulting in the enhanced optical absorption from UV into visible light. This theoretical predictions provide insightful outlooks in understanding the effects of interface and doping on the enhanced photocatalytic property of the g-C3 N4 /g-ZnO nanocomposites, which will assist in engineering highly efficient g-C3 N4 -based photocatalysts.